JUAL BELI MELALUI E-COMMERCE DI PASAR SAIL KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Fitria Kusumawardhani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The purpose of this study is to understand and identify Buying and Selling Through E-Commerce in the Sail Market Pekanbaru City Based on the Law of the Republic of Indonesia Number 19 of 2016 concerning Information and Electronic Transactions. This research method is Sociological Law, Sociological Approach Approach which is an Analyzing Approach About How to Buy and Sell E-Commerce in Sail City Market Pekanbaru. The total population of 100 and a random sample is 3 traders who are victims of e-commerce scams that harm traders to buy and sell directly to consumers. The purpose of this study is for writers and the public to know and understand Law Number 19 of 2016 concerning Information and Electronic Transactions. The results of this study indicate that the level of confidence of retailers in online purchases is very small and prone to fraud so traders choose to buy and sell directly to avoid fraud against merchandise.